Changes in Agriculture Land Usage for Development of Housing (Studies in Tambakrejo Village Jombang District) - Andri, Muhammad; Winarsih, Rini; Rafiie, Mohammad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The rise of housing development by developers on active agricultural land means the government must ensure national food security. Although Law No. 41 of 2009 concerning Protection of Sustainable Food Agricultural Land has been enacted, the reality is that in many cities many agricultural lands close to urban areas have been converted into residential areas. This is the background for the author to examine